Orbital-level band gap engineering of RuO2 for enhanced acidic water oxidation - Xing Wang; Wei Pi; Zhaobing Li; Sheng Hu; Haifeng Bao; Weilin Xu; Na Yao (Nature Communications)
Abstract Developing efficient and stable oxygen evolution reaction electrocatalysts under acidic conditions is crucial for advancing proton-exchange membrane water electrolysers commercialization. Here, we develop a representative strategy through p-orbital atoms (N, P, S, Se) doping in RuO2 to precisely regulate the lattice oxygen-mediated mechanism-oxygen vacancy site mechanism pathway. In situ and ex situ measurements along with theoretical calculations demonstrate that Se doping dynamically adjusts the band gap between the Ru-e g and O-p orbitals during the oxygen evolution reaction process. This modulation accelerates electron diffusion to the external circuit, promotes the lattice oxygen-mediated process, and enhances catalytic activity. Additionally, it facilitates electron feedback and stabilizes oxygen vacancies, thereby promoting the oxygen vacancy site mechanism process and enhancing catalytic stability. The resulting Se-RuOx catalyst achieves efficient proton-exchange membrane water electrolysers performance under industrial conditions with a minimal charge overpotential of 1.67 V to achieve a current density of 1 A cm−2 and maintain long-term cyclability for over 1000 h. This work presents a unique method for guiding the future development of high-performance metal oxide catalysts.